Analisis Komunikasi Bisnis Pada Toko Distro Warcloth dalam Meningkatkan Kemitraan dengan Supplier - Sopiansyah, Rochmat; Firmansyah, Ricky; Permatasari, Yulianti; Kusumah, Rida Natalia; Anjani, Riska (Jurnal Ilmu Komunikasi, 2024)
Poor business communication between a company and its suppliers can have fatal consequences on the inventory of goods and the quality of products that do not meet the required standards due to inadequate communication of raw materials for a product. Poor business communication can also reduce the trust between the supplier and the company, leading to contract termination. The purpose of this study is to explore the significance of business communication in strengthening partnership relationships with suppliers. This study was conducted using qualitative research methods, including interviews with the Warcloth Distro Store, which has a good partnership with its supplier. The results of this study show that effective business communication plays a crucial role in building a strong partnership with suppliers at the Warcloth Distro Store. In a successful partnership, companies and suppliers communicate regularly to ensure the availability of inventory, product quality, and reasonable prices. Communication also helps reduce uncertainty, increase trust, and form long-term partnerships that are mutually beneficial for both parties.